Can Communication Mitigate Strategic Delays in Investment Timing? - Ayse Gül Mermer; Sander Onderstal; Joep Sonnemans (Tinbergen Institute, 2022)
In economic environments, decision-makers may strategically delay irreversible investments to learn from the actions of others creating socially suboptimal outcomes. We investigate if and how communication mitigates the strategic delay in investment timings. Players choose when to invest in a nonrival project with uncertain returns. The earliest investor bears the costs of investment and all players learn whether the project is of good or bad quality. Informational externalities create free-riding incentives resulting in strategic delays in investment timings. Our theoretical analysis suggests that introducing communication into this setting reduces strategic delay. We implement our model in a laboratory experiment utilizing a 2x2 design, where we vary the availability of communication and the number of agents. We find that communication significantly reduces the strategic delay and leads to earlier investment timings in the two-player case. In the case of four players, communication helps subjects to coordinate and reduce strategic delay significantly in the first period of the experiment, while coordination failures emerge in the following periods sweeping away the beneficial effect of communication at the aggregate level.
Keywords: C71; C92; D83; L40; 330; Investment Timing; Strategic Delay; Communication; Coordination; Informational; Externalities; Experiments